The Occurrence of a Difference Between the Actual Transaction Price and the Transaction Price Listed in the Notary's Deed of Sale and Purchase in Semarang Regency - Zahra, Nabila Kartika; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. The land sale and purchase process must be made in the form of an authentic deed made by an authorized official, in this case a Notary and/or PPAT (Land Deed Making Official). In a sale and purchase, there is a transaction price that must be stated in the deed. However, the price stated in the Sale and Purchase Agreement deed does not match the actual transaction price. The purpose of this study is to analyze: 1) Why There Is a Difference Between the Actual Transaction Price and the Transaction Price Listed in the Deed of Sale and Purchase Agreement. 2) How to Anticipate So That There Is No Difference Between the Actual Transaction Price and the Transaction Price Listed in the Deed of Sale and Purchase Agreement.This type of research is empirical legal research. The approach method in this research is a Qualitative approach. The types and sources of data in this research are primary and secondary data obtained through interviews and literature studies. The analysis in this research is Descriptive Analytical. The results of the study found that the factor of the difference in transaction prices was to avoid high taxes so that the parties wanted to include a cheaper price in the Notary Sale and Purchase Agreement compared to the actual transaction price. To anticipate this, namely by integrating the National Land Agency (BPN) with the Regional Finance Agency (BKUD), this will make it easier to carry out land sales and purchases.Keywords: Buying; Notary; Selling; Transaction.